Jews and Gentiles - Himmelfarb, Milton (Encounter Books, 2007)
"Includes information on anti-Semitism, art, Bible, capitalism, Catholics, Christianity, Christian Right, communists, Declaration of Independence, Democratic Party, demography, France, Germany, Great Britain, Hasidim, Hebrew language, Adolf Hitler, Holocaust, Islam, Israel, Moses Maimonides, Marxism, Moses Mendelssohn, Walter Mondale, Moral Majority, Muslims, Gamal Abdel Nasser, Nazis, Orthodox Judaism, Poland, rabbis, race relations, Ronald Reagan, Reform Judaism, Republican Party, Russia, Sabbath, Jean-Paul Sartre, Sephardim, William Shakespeare, Six-Day War, Soviet Union, Baruch Spinoza, Josef Stalin, Leo Strauss, tax policy, Torah, U.S. Constitution, Yiddish, Yom Kippur, Zionism, etc."--From source other than the Library of Congress